PENGEMBANGAN ASESMEN MADRASAH DINIYAH MELALUI BALANCED SCORECARD - Abu Muslim; Ulfa Binti Arafah (LPPM IAI Hasanuddin Pare-Kediri, 2022)
In this article, the author examines and analyzes how madrasah diniyah implement the Balanced Scorecard or balanced scorecard to get to a better madrasa by using the four perspectives of the balanced scorecard. This study begins with the problem of madrasah diniyah that have not maximized the Balanced Scorecard in the assessment of madrasah diniyah. Overcoming this problem according to the author becomes something that if you base it as a madrasah diniyah manager with a Balanced Scorecard which has four balance scorecards consisting of a financial perspective, a customer perspective, an internal process perspective and a learning and growth perspective. Seeing the current condition of Islamic education, it is necessary to balance efforts so that madrasas are not eroded by the times. The conclusion of this study is the Balanced Scorecard is a management concept that translates tactics into action. starting from the vision and strategic institutions, from various important success factors so that madrasah diniyah can face competition in the world of education. So that madrasah diniyah have economic value as well as social value for the sake of continuity of service (substansibility).